Effects of stochastic fluctuations at molecule-electrode contacts in transition voltage spectroscopy - Bâldea, Ioan (Chemical physics, 2012)
The influence of the stochastic fluctuations at contacts on the electron transport through molecular junctions based on alkanedithiols is investigated theoretically. Results are presented, which demonstrate that the transition voltage Vt is insensitive to fluctuations in the electrode-molecule hopping integrals. By contrast, reasonably large fluctuations (δJ∼2eV) in the Coulomb contact interaction J, included via an extended Newns-Anderson model, lead to fluctuations in the molecular orbital energetic alignment ε0, which are consistent with the fluctuations in Vt observed experimentally. The impact of these J- (or ε0-) fluctuations on the conductance G is considerably stronger than on Vt. The G-fluctuations driven by δJ represent a substantial fraction of the fluctuations displayed by experimental conductance histograms. The electron system for J≠0 is correlated, i.e., it cannot be described within a single-particle (Landauer-based) picture. However, in the J-range of interest, the ratio Vt/ε0 turns out to be only weakly dependent on J. The weak impact of J on the ratio Vt/ε0 is important because it suggests that, even in the presence of realistically strong electron correlations, transition voltage spectroscopy can be a useful tool of investigation.